Desenvolvimento de grama-esmeralda, grama-bermudas 'Tifway 419' e 'Celebration' submetidas a aplicação de reguladores de crescimento - Zanon, Maurício Ercoli [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The implementation and management of sports fields is among the agricultural activities of high technology. The ornamental point of view, the lawns are one of the most important landscape components. Its constant maintenance becomes an expensive operation and often mowing operations can offer the risk of accidents. Therefore, it is very important to search for alternatives for reducing the frequency of mowing and one of them is the use of growth regulators. Thus, this study had as objective to evaluate the efficiency of doses of growth regulators, Paclobutrazol and trinexapac-ethyl on the vegetative growth of zoysiagrass (Zoysia japonica), bermudasgrass 'Tifway 419' (Cynodon dactylon x Cynodon transvaalensis) and bermudasgrass 'Celebration' (Cynodon dactylon) under field conditions as an alternative to traditional management performed through cuts weekly. The experiment was conducted in a commercial production area of grass located in the Fazenda São José, municipality of Jardinópolis / SP, in the period from October to December 2013. The experimental design was a randomized block; there were eight treatments (control 1: no pruning; witness 2: pruning weekly, three Paclobutrazol doses: 70, 140 and 280 g ha-1; three trinexapac-ethyl: 100, 200 and 400 g ha-1). It was performed a single application of the product and the irrigation was conducted followed the technique used in the company which allocated the area for this experiment. Ratings were made at 15, 30, 45 and 60 days after application being evaluated height (cm); dry mass of shoots; dark green color index (ICVE) and quality (notes). It was found that the Paclobutrazol at the dosages tested, was not effective to suppress the zoysiagrass growth and did not affect the quality of the lawn.On the contrary, trinexapac-ethyl was effective in suppressing growth of this grass, mainly in the dose of 400 g ai ha-1, which showed a decrease in growth efficiency up to 45 days ...

A implantação e manejo de gramados esportivos está entre as atividades agrícolas de mais alta tecnologia. Do ponto de vista ornamental, os gramados constituem um dos componentes paisagísticos mais importantes. A sua manutenção constante torna-se uma operação onerosa e muitas vezes, as operações de poda podem oferecer riscos de acidentes. Desta forma, é muito importante a busca de alternativas que visem diminuir a frequência das podas e uma delas é o uso de reguladores de crescimento. Sendo assim, este trabalho teve como objetivo avaliar a eficiência de doses dos reguladores de crescimento, paclobutrazol e trinexapac-ethyl, no crescimento vegetativo de grama-esmeralda (Zoysia japonica), grama-bermudas 'Tifway 419' (Cynodon dactylon x Cynodon transvaalensis) e grama-bermudas 'Celebration' (Cynodon dactylon) em condições de campo como alternativa ao manejo tradicional realizado por meio de podas semanais. O trabalho foi realizado em uma área de produção comercial de grama localizada na Fazenda São José, município de Jardinópolis/SP, em 2013. Foi realizado um experimento para cada grama e em todos, o delineamento experimental foi o de blocos ao acaso; foram oito tratamentos (testemunha 1: sem poda; testemunha 2: poda semanal; três doses de paclobutrazol: 70, 140 e 280 g ha-1; três doses de trinexapac-ethyl: 100, 200 e 400 g ha-1) e quatro repetições. Foi realizada uma única aplicação dos produtos. Foram efetuadas avaliações aos 15, 30, 45 e 60 dias após a aplicação sendo avaliadas altura (cm); massa seca da parte aérea; Índice de Cor Verde Escuro (ICVE) e qualidade (notas). Verificou-se que o paclobutrazol, nas doses testadas, não foi efetivo para suprimir o crescimento de grama-esmeralda e também não afetou a qualidade do gramado; ao contrário, trinexapac-ethyl foi efetivo na supressão do crescimento desta grama, principalmente na dose de 400 g i.a. ha-1, que mostrou eficiência de redução...
Keywords: Gramados; Gramínea; Crescimento (Plantas); Plantas - Reguladores; Produtos químicos agrícolas; Lawns